Decolonisation, Globalisation and South Africa 1 - Liepollo Pheko (International Journal of Critical Diversity Studies)
This article analyses whether South Africa can decolonise its economic architecture in the era of globalisation. It further argues that South Africa’s 1994 debut into global economic polity is hampered by Western-framed globalisation, which further re-inscribes evolving colonial constructs. However, this article presents the theoretical frameworks of Afrikanisation and Pan-Afrikanisation as strategies which offer South Africa the difficult possibility of reclamation. Whilst there are challenges in pursuing this, the article suggests that a reorientation away from capitalist globalisation will be better facilitated by inward-looking Afrikan epistemologies through which the ongoing work of decolonisation is a crucial anchor. These include humanism conceptualised by Kenneth, Scientific Socialism conceptualised by Kwame Nkrumah and the Arusha Declaration spearheaded by Julius Nyerere ( Kanu, 2014 ). This article further discusses the concepts of global capitalism and decolonisation and centres them under the rubric of globalisation studies, including the neo-liberalisation of that field. Within this discourse, this article explores whether a contemporary Afrikan 2 state like South Africa can be delinked from economic globalisation, which represents another complex colonial stronghold. It explores the logic of racialised colonialism and its impact on South Africa and draws on the works of decolonial theorists of the twentieth-century anti-imperialist era.